FACTORS AFFECTING CAPITAL STRUCTURE: A STUDY AMONG MANUFACTURING COMPANIES OF CONSUMER GOODS IN INDONESIA - Anggraini, Nita; Sha, Thio Lie (International Journal of Application on Economics and Business, 2023)
This research aimed to obtain empirical evidence about the effects of tax, asset structure, business risk, and profitability on. capital structure in the manufacturing companies’ consumer goods sector listed on the Indonesia Stock Exchange during 2018-2020. The research method was descriptive research using quantitative. This research used 96 data that had been selected by using the purposive sampling method. Data analysis technique was done using a multiple linear regression analysis with EViews Software version 12. The results found that asset structure had negative and significant effect on the capital structure, while the tax, business risk, profitability had no significant effect on capital structure.